PERBEDAAN SIKAP TENTANG KONTRASEPSI SUNTIK MENURUT TINGKAT PENGETAHUAN AKSEPTOR KELUARGA BERENCANA DENGAN METODE SUNTIK - , NOVI KARTIKA WULANDARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background : Injectable contraceptive is the most widely contraceptive method used in Indonesia. The average level of knowledge of contraceptive methods acceptor all good, but in some areas obtained different results. Good knowledge of contraceptive acceptors will tend to choose a rational contraceptive method. Through the level of knowledge about contraception it can be seen how the attitude of the acceptor on the sustainability of the use of an injectable. Objective : This study aimed to determine differences in attitudes about injectable contraceptives according to the level of knowledge of family planning acceptors with the injection method. Methods : The study was conducted with a cross-sectional design. The experiment was conducted from March to May 2014 in the countryside of Kedungwinong, District of Nguter, Sub-province of Sukoharjo. The respondents were participated in this study as many 66 respondents. The research instrument is a questionnaire that contains three kinds of questions that is: respondent characteristics, knowledgeâs questionnaire and attitudeâs questionnaire about injectable contraceptives. Data were analyzed used statistical program of Wilcoxonâs test. Results : Characteristics of respondents injectable contraceptives by age 78.8% in the age range 20-35 years, education 56.0% primary education, work 51.1% is housewife. While based on a parity as much as 62.1% had 2 childrens. Injection type as many as 81.8% chose 3-month injectable. For resources 84.8% obtained through health professionals. For a history of contraception by 77.3% never use another contraceptive method. The level of knowledge of most of the respondents are enough as many as 62.2%. Attitudes toward injectable contraceptives as many as 95,5% had an attitude in favor. Statistical test results showed there was differences in attitudes about injectable contraceptives according to the level of knowledge of family planning acceptors with injection method (p = 0.000). Conclusions: There was difference in attitudes about injectable contraceptives according to the level of knowledge of family planning acceptors with the injection method.